“Traces of my tears will remain on this paper ...”: Letters from Elizabeth Stephens to M. M. Speransky - K. A. Sozinova (Научный диалог, 2020)
The author of the article assumes that the interstate relations between Russia and Great Britain in the late 18th — early 19th centuries largely determined the area of private contacts between Russians and the British. English-Russian marriages have a special place in the history of English-Russian relations. Attention is paid to one of such unions — the marriage of the outstanding statesman M. M. Speransky with an Englishwoman Elizabeth Stephens. It is claimed that a significant role in Speransky’s fate was played by A. A. Samborsky, also married to an Englishwoman, in whose house Speransky’s fateful meeting with his future wife took place. It is reported that the Speransky Fund of the Russian national library preserved letters of Elizabeth Stephens to Speransky, previously not widely attracted by researchers, but not all of these letters actually belong to Elizabeth, some of them belong to her sister — Marianne. This study provides the first translation of these letters for the analysis of Speransky’s private life. The author concludes that the preserved correspondence meets the standards and methods of expression of feelings in the era of “sentimentalism.” The problem of how much Speransky was immersed in the cultural context of British reality due to this marriage is also considered. Despite the fact that the marriage was quite short, Speransky’s relations with the Stephens family were quite strong.